Penerapan Internet of Things pada Sistem Monitoring Suhu dan Kelembaban Ruang Server Menggunakan Node MCU ESP 8266 - Kristiawan, Agus; Tarigan, Masmur (Jurnal Teknik Informatika dan Komputer, 2025)
A server is a room used to store computer equipment. Currently, at PT SIK, the server room only uses a thermo controller to display the actual temperature inside the server room, and it is only installed within the room, making it impossible to monitor directly. Another issue is that the Air Conditioner in the server room turns off suddenly, causing the temperature to rise. Additionally, the server room administrator works 24/7 and cannot anticipate any possible failures in the server room's Air Conditioner. The researcher will attempt to collect, record, and process data on the server room temperature using a DHT22 temperature and humidity sensor connected to a NodeMCU ESP8266 microcontroller, which is connected to the internet and can send real-time notifications to the server room administrator. On the smartphone side, the Blynk application is used to view temperature and humidity graphs and to receive notifications when there is an abnormal condition in the server room.